2012
DOI: 10.1097/mpg.0b013e3182333f18
|View full text |Cite|
|
Sign up to set email alerts
|

Human Milk Probiotic Lactobacillus fermentum CECT5716 Reduces the Incidence of Gastrointestinal and Upper Respiratory Tract Infections in Infants

Abstract: Administration of a follow-on formula with L. fermentum CECT5716 may be useful for the prevention of community-acquired gastrointestinal and upper respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 27 publications
10
179
0
13
Order By: Relevance
“…IF and FOF containing "probiotics" have also been studied in relation to any potential untoward effects, such as delayed growth, diarrhoea and allergic reactions (Braegger et al, 2011;Gil-Campos et al, 2012;Maldonado et al, 2012;Azad et al, 2013). It has been generally concluded that currently evaluated "probiotic"-supplemented IF do not raise safety concerns with regard to growth or other adverse effects, although in many studies adverse events were inconsistently reported (Azad et al, 2013) and further evaluations of safety in long-term studies are needed (Braegger et al, 2011).…”
Section: "Probiotics" and "Synbiotics"mentioning
confidence: 99%
“…IF and FOF containing "probiotics" have also been studied in relation to any potential untoward effects, such as delayed growth, diarrhoea and allergic reactions (Braegger et al, 2011;Gil-Campos et al, 2012;Maldonado et al, 2012;Azad et al, 2013). It has been generally concluded that currently evaluated "probiotic"-supplemented IF do not raise safety concerns with regard to growth or other adverse effects, although in many studies adverse events were inconsistently reported (Azad et al, 2013) and further evaluations of safety in long-term studies are needed (Braegger et al, 2011).…”
Section: "Probiotics" and "Synbiotics"mentioning
confidence: 99%
“…A few studies used bacteria isolated from HM. 138,139 Several reasons have been used to support probiotic use in infant formula. Human milk, as previously described, contains a variety of potential probiotic bacteria, such as Bifidobacterium, Lactobacillus and Streptococcus, and these bacteria serve as a source of continuous inoculum to the BF infant GI tract, which may partly contribute to differences in the fecal microbial composition between BF and FF infants.…”
Section: Probioticsmentioning
confidence: 99%
“…The most recent QPS Opinion is cited by Adimpong et al (2012) and Bourdichon et al (2012a,b). In other publications this is not always the case (Ambalam et al, 2012;Baffoni et al, 2012;Bonaterra et al, 2012;Bosch et al, 2012;Chaabouni et al, 2012;Christoffersen et al, 2012;Danilova et al, 2012;El-Sharoud et al, 2012;Gálvez et al, 2012;Gardana et al, 2012;Hill, 2012;Maldonado et al, 2012;Nikolic et al, 2012;Permpoonpattana et al, 2012;Popova et al, 2012;Salminen and van Loveren, 2012;Songisepp et al, 2012;Stahl and Barrangou, 2012;Thumu and Halami, 2012;Vogel et al, 2011;Xu et al, 2012).…”
Section: Reference To Qps In the Scientific Literaturementioning
confidence: 96%